Proposta metodológica para compensação das emissões de metano não queimado em motores de ignição por compressão do tipo duplo combustível a diesel e gás natural veicular - Massagardi, Mário Angelo (2014)
This work proposes a methodological approach for the compensation of the residual unburned methane emissions, generated during the combustion process of dual-fuel, compression ignition engines, using diesel and compressed natural gas (CNG) as fuels. Its concept was conceived under the logic of the greenhouse gases balance among dual-fuel and its “parent” diesel engine. The dual - fuel diesel - CNG engines are a new developing technology that allows the use of CNG with energy efficiency comparable to diesel engines, enabling its use in commercial vehicles in both economical and operational viewpoints. Additionally, these engines, in their state of the art, have technology enough to meet all the legal limits for emissions of toxic exhaust gases, in special the particulate matter limit, which is met with advantages over diesel engines.. Therefore, theoretical models were created to quantify the carbon dioxide emission reduction in relation to the different diesel-CNG fuel proportions used in the dual-fuel engine. On this basis, the emission of methane that would be compensated were defined. Additionally, the proposed theoretical methodology was tested in a real experiment with a Diesel-CNG engine, tested in the European transient cycle (ETC) to meet Euro V certification, which confirmed its practical applicability. The survey also sought to analyze the main characteristics of the dual - fuel Diesel-CNG technology, describing and quantifying their behavior in energy efficiency and emissions of toxic exhaust components by comparing them with CNG and diesel engines. The developed methodology is, therefore, a feasible criterion to adapt both Brazilian and European emission standards by creating specific dual-fuel Diesel-GNV engine certification limits, and allow the efficient use of Natural Gas in commercial vehicles.